1990
DOI: 10.1021/jm00172a025
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific synthesis, assignment of absolute configuration, and biological activity of the enantiomers of 3-[[[3-[2-(7-chloroquinolin-2-yl)-(E)-ethenyl]phenyl][[3-(dimethylamino)-3-oxopropyl]thio]methyl]thio]propionic acid, a potent and specific leukotriene D4 receptor antagonist

Abstract: The enantiomers of the leukotriene D4 antagonist 3-[[[3-[2-(7-chloroquinolin-2-yl)-(E)-ethenyl]phenyl] [[3-(dimethylamino)-3-oxopropyl]thio]methyl]thio]propionic acid (L-660,711)(MK-571) have been prepared, their absolute stereochemistry has been assigned as S for (+)-1 and R for (-)-1 by X-ray analysis of a synthetic intermediate (5), and the biological activity of the enantiomers has been explored. Unexpectedly, the enantiomers are both comparably biologically active with (+)-1 slightly more intrinsically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In literature it is reported that a number of quinoline derivatives possesses antileishmanial, [1] cytotoxicity, [2] antituberculosis, [4] antimalarial, [5] anti-inflammatory [6] and HIV-1 Integrase Inhibitors. [7] Quinoline derivatives have been developed for the treatment of many diseases like malaria, [8] HIV, [9] tumor [10] and antibacterial infections [11] and some of the substituted quinolines have been reported to act as leukotriene D4 receptor, [12] 5HT3, [13] antagonists for endothelin [14] and NK-3. [15] They also function as 5lipoxygenase, [16] dihydroorotate dehydrogenase [17] and inhibitors of gastric (H+/K+)-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…In literature it is reported that a number of quinoline derivatives possesses antileishmanial, [1] cytotoxicity, [2] antituberculosis, [4] antimalarial, [5] anti-inflammatory [6] and HIV-1 Integrase Inhibitors. [7] Quinoline derivatives have been developed for the treatment of many diseases like malaria, [8] HIV, [9] tumor [10] and antibacterial infections [11] and some of the substituted quinolines have been reported to act as leukotriene D4 receptor, [12] 5HT3, [13] antagonists for endothelin [14] and NK-3. [15] They also function as 5lipoxygenase, [16] dihydroorotate dehydrogenase [17] and inhibitors of gastric (H+/K+)-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…The quinoline scaffold has been identified among privileged ones in drug discovery . In particular, quinoline derivatives can be found among antimalarial, antibacterial, antiasthmatic, antihypertensive, and anti-inflammatory agents. Aryl-substituted quinolines act as ligands for 5-lipoxygenase, tyrosine kinase (PDGF-RTK), leukotriene, LTD 4 , and other receptors. Furthermore, polyquinolines were shown to undergo hierarchical self-assembly into nanostructures with promising electronic and photonic properties …”
Section: Introductionmentioning
confidence: 99%
“…This particular quinoline nucleus is widespread among biologically active compounds, such as antitumor agents, CysLT (LTD4) receptor antagonists, antileishmanial agents, and HIV-1 replication inhibitors and was recently reported as a scaffold for promising new PDE4 inhibitors . Several syntheses of quinolines bearing different substitution patterns and amenable to small library production using solution phase approaches or solid-phase techniques have been published recently.…”
Section: Introductionmentioning
confidence: 99%